PERAN KEPALA DESA TERHADAP PERLINDUNGAN BAGI PENGGARAP DALAM SISTEM BAGI HASIL PERTANIAN DI DESA - Anita Kamilah; M Rendi Aridhayandi; Safa Naadiyah Nurwidad (Universitas Suryakancana, 2023)
The regulation regarding production sharing agreements in Indonesia has been regulated based on Law Number 2 of 1960 concerning Revenue Sharing Agreements, the profit sharing agreements that occurred in the Nagrak Village Area, Cianjur District, Cianjur Regency, the arrangement still uses the arrangement of profit sharing agreements according to local customary law. The role of the Village Head in this case is very necessary so that there is no dispute between the two parties in the implementation of the agricultural land production sharing agreement. As for the identification of the problem in this research, namely, whether the production sharing system for agricultural land in Nagrak Village, Cianjur District, Cianjur Regency has complied with the provisions of Law Number 2 of 1960 concerning Production Sharing Agreements? in Nagrak Village, Cianjur District, Cianjur Regency?, and what steps did the Head of Nagrak Village, Cianjur District, Cianjur Regency take in resolving the obstacles faced by farmers and cultivators in the agreement for agricultural land yields?. This research uses a normative juridical approach, which examines juridical data on the application of agricultural land production sharing agreement regulations. It is concluded that the regulation regarding production sharing agreements for agricultural land in Indonesia is still using Law Number 2 of 1960 concerning Production Sharing Agreements. The form of the agreement is made in writing before the Village Head and ratified by the Camat, but in practice Law Number 2 of 1960 concerning Profit Sharing Agreements is still not effective this is due to the ignorance of the local community with the existence of Law Number 2 of 1960 concerning Agreements Profit sharing.Keywords: Profit Sharing Agreement, Role of Village Head, Agricultural Land.